Good Corporate Governance, Corporate Value, Tax Avoidance and Financial Performance - Risa, Nurma (Magister of Accounting, 2018)
If a company applies GCG practices it will have an impact on the value of the company. But the implementation of GCG alone is actually not enough to increase the value of the company, there are other things, namely the practice of tax avoidance and financial performance. This study aims to prove that tax avoidance and financial performance practices are intermediary variables in the relationship of GCG to corporate value. The sample of this study is companies that take the IICG survey and have CGPI scores, and are listed on the stock exchange in the period of 2012 - 2015. Path analysis is used as a method of data analysis. The results of the study show that the GCG practices influence the value of the company indirectly, but through the practice of tax avoidance and financial performance as intermediaries.